Automated reporting of pharmacokinetic study results: gaining efficiency downstream from the laboratory. (July 2011) - Schaefer, Peter
The purpose of bioanalysis in the pharmaceutical industry is to provide 'raw'' data about the concentration of a drug candidate and its metabolites as input for studies of drug properties such as pharmacokinetic (PK), toxicokinetic, bioavailability/bioequivalence and other studies. Building a seamless workflow from the laboratory to final reports is an ongoing challenge for IT groups and users alike. In such a workflow, PK automation can provide companies with the means to vastly increase the productivity of their scientific staff while improving the quality and consistency of their reports on PK analyses. This report presents the concept and benefits of PK automation and discuss which features of an automated reporting workflow should be translated into software requirements that pharmaceutical companies can use to select or build an efficient and effective PK automation solution that best meets their needs.